"He thought the Māori did not use their land ...": the Wastelands in 1840s landscape painting [propaganda] - Schmidt, Tyson (Architectural History Aotearoa, 2014)
The waste lands concept was an important part of the colonial project, gaining particular traction in the 1850s. Its initial implementation in New Zealand was begun in the 1840s, underpinning a strongly economic approach to settlement favoured by the owners and proprietors of the New Zealand Company. In the 2012 version of this symposium I presented a paper that explored how images of New Zealand's landscape in the 1850s could be analysed in light of the concept, with a particular focus on Crown/Māori relationships. Here I extend this analysis into the 1840s – before the heady heights of waste land policy implementation – and test what landscape images from the likes of William Fox, Charles Heaphy, and publications such as Edward Jerningham Wakefield's Adventures in New Zealand can reveal when read through the lens of the waste lands concept.